Negative electrode active material for non-aqueous electrolyte secondary battery and method for manufacturing the same
By adding silicide, lithium compound and titanium carbon to the negative electrode battery active material of the nonaqueous electrolyte secondary battery, the problem of poor stability of the negative electrode battery is solved, and the battery is high efficiency and long life is achieved.
Patent Information
- Application Number
- JP2023178673
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2043-10-17
AI Technical Summary
The prior art is difficult to stabilize the silicon-based negative electrode active material when producing the negative electrode slurry of a nonaqueous electrolyte secondary battery, resulting in poor battery cycle performance and primary charge and discharge efficiency.
Using an anode battery active material containing silicide (SiO)x (0.5≦x≦1.6), lithium compounds are added, and the surface of the material is coated with titanium-like carbon (diamond-like carbon) or other carbon materials. The G-band peak of the carbon material is in the range of 1530 cm-1 to 1590 cm-1, and the carbon coverage is between 0.5% and 10%.
Through the improved negative electrode battery active material, the battery capacity, cycle performance and primary charge and discharge efficiency are significantly improved, the stability of the slurry is enhanced, the gas generation at high temperature is reduced, and the feasibility of industrial production is improved.
Smart Images

Figure 2025068713000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode active material for a non-aqueous electrolyte secondary battery and a method for producing the same. [Background technology]
[0002] In recent years, small electronic devices such as mobile terminals have become widespread, and there is a strong demand for further miniaturization, weight reduction, and longer life. In response to such market demands, development of secondary batteries that are small, lightweight, and capable of obtaining high energy density has been promoted. The application of these secondary batteries is being considered not only for small electronic devices, but also for large electronic devices such as automobiles and power storage systems such as homes.
[0003] Among these, lithium-ion secondary batteries are attracting great attention because they can be easily made small and have a high capacity, and because they offer a higher energy density than lead-acid batteries and nickel-cadmium batteries.
[0004] The lithium ion secondary battery includes a positive electrode, a negative electrode, a separator, and an electrolyte solution, and the negative electrode contains a negative electrode active material involved in charge and discharge reactions.
[0005] While carbon-based active materials are widely used as negative electrode active materials, recent market demands have called for further improvements in battery capacity. To improve battery capacity, the use of silicon as a negative electrode active material is being considered. This is because the theoretical capacity of silicon (4199mAh / g) is more than 10 times greater than that of graphite (372mAh / g), and a significant improvement in battery capacity can be expected. In the development of silicon materials as negative electrode active materials, not only silicon itself but also alloys and compounds such as oxides are being considered. In addition, the active material shape is being considered, ranging from the standard coating type for carbon-based active materials to an integrated type that is directly deposited on the current collector.
[0006] However, when silicon is used as the main raw material for the negative electrode active material, the negative electrode active material expands and contracts during charging and discharging, making it prone to cracking, mainly near the surface layer of the negative electrode active material. In addition, ionic substances are generated inside the active material, making the negative electrode active material prone to cracking. When the surface layer of the negative electrode active material cracks, a new surface is formed, and the reaction area of the active material increases. At this time, a decomposition reaction of the electrolyte occurs on the new surface, and a coating, which is a decomposition product of the electrolyte, is formed on the new surface, consuming the electrolyte. This makes the cycle characteristics prone to deterioration.
[0007] To date, various studies have been conducted on negative electrode active materials and electrode configurations for lithium-ion secondary batteries that are primarily made of silicon materials in order to improve the initial battery efficiency and cycle characteristics.
[0008] Specifically, in order to obtain good cycle characteristics and high safety, silicon and amorphous silicon dioxide are simultaneously deposited using a gas phase method (see, for example, Patent Document 1). Also, in order to obtain high battery capacity and safety, a carbon material (electron conductive material) is provided on the surface layer of silicon oxide particles (see, for example, Patent Document 2). Furthermore, in order to improve cycle characteristics and obtain high input / output characteristics, an active material containing silicon and oxygen is prepared, and an active material layer with a high oxygen ratio is formed near the current collector (see, for example, Patent Document 3). Also, in order to improve cycle characteristics, oxygen is contained in the silicon active material, and the active material is formed so that the average oxygen content is 40 at% or less and the oxygen content is high in the area close to the current collector (see, for example, Patent Document 4).
[0009] In addition, in order to improve the initial charge / discharge efficiency, the Si phase and SiO 2 In order to improve cycle characteristics, a nanocomposite containing a metal oxide, MyO, is used (see, for example, Patent Document 5). x(0.8 ≤ x ≤ 1.5, particle size range = 1 μm to 50 μm) is mixed with a carbon material and fired at a high temperature (see, for example, Patent Document 6). Further, in order to improve cycle characteristics, the molar ratio of oxygen to silicon in the negative electrode active material is set to 0.1 to 1.2, and the active material is controlled within a range where the difference between the maximum value and the minimum value of the molar ratio near the interface between the active material and the current collector is 0.4 or less (see, for example, Patent Document 7). Further, in order to improve the battery load characteristics, a metal oxide containing lithium is used (see, for example, Patent Document 8). Further, in order to improve cycle characteristics, a hydrophobic layer such as a silane compound is formed on the surface layer of the silicon material (see, for example, Patent Document 9).
[0010] Further, in order to improve cycle characteristics, silicon oxide is used, and conductivity is imparted by forming a graphite film on its surface layer (see, for example, Patent Document 10). In Patent Document 10, regarding the shift value obtained from the RAMAN spectrum of the graphite film, broad peaks appear at 1330 cm -1 and 1580 cm -1 , and the intensity ratio I 1330 / I 1580 is such that 1.5 < I 1330 / I 1580 < 3. Further, in order to improve high battery capacity and cycle characteristics, particles having a silicon microcrystalline phase dispersed in silicon dioxide are used (see, for example, Patent Document 11). Further, in order to improve overcharge and overdischarge characteristics, a silicon oxide in which the atomic ratio of silicon to oxygen is controlled to 1:y (0 < y < 2) is used (see, for example, Patent Document 12).
[0011] When using a silicon material as the negative electrode active material, a high initial efficiency and capacity retention rate can be obtained by using a silicon material doped with Li. On the other hand, the silicon material doped with Li has low stability in aqueous solvents, and the stability of the aqueous negative electrode slurry mixed with the silicon material produced during the production of the negative electrode is reduced, making it industrially unsuitable. In order to improve the stability of the aqueous negative electrode slurry, water resistance is increased by attaching a phosphate to the outermost layer of the silicon material doped with Li (see, for example, Patent Document 13). However, the stability of the aqueous negative electrode slurry is insufficient, as gas generation is observed during high-temperature storage of the aqueous negative electrode slurry. Therefore, a technology has been reported that suppresses gas generation during high-temperature storage of the aqueous negative electrode slurry by optimizing the amount of phosphate (see, for example, Patent Document 14). However, a technology for suppressing gas generation in a slurry containing a negative electrode active material, a binder component, a conductive assistant, etc., and a technology for suppressing gas generation under harsh conditions when only a silicon-based active material is placed in water has not yet been established. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] JP 2001-185127 A [Patent Document 2] JP 2002-042806 A [Patent Document 3] JP 2006-164954 A [Patent Document 4] JP 2006-114454 A [Patent Document 5] JP 2009-070825 A [Patent Document 6] JP 2008-282819 A [Patent Document 7] JP 2008-251369 A [Patent Document 8] JP 2008-177346 A [Patent Document 9] JP 2007-234255 A [Patent Document 10] JP 2009-212074 A [Patent Document 11] JP 2009-205950 A [Patent Document 12] Japanese Patent Application Publication No. 06-325765 [Patent Document 13] JP 2017-152358 A [Patent Document 14] JP 2020-77510 A Summary of the Invention [Problem to be solved by the invention]
[0013] As mentioned above, in recent years, small electronic devices such as mobile terminals have become more powerful and multifunctional, and there is a demand for increased battery capacity for the lithium-ion secondary batteries that serve as their main power sources. As one method for solving this problem, there is a demand for the development of lithium-ion secondary batteries with a negative electrode that uses silicon material as the main material.
[0014] In addition, when using silicon materials, high initial efficiency and capacity retention can be obtained by using Li-doped silicon materials, but on the other hand, Li-doped silicon materials have low stability in aqueous solvents, which reduces the stability of the aqueous negative electrode slurry prepared when mixing the silicon material during negative electrode production, making them industrially unsuitable. In order to stabilize the aqueous negative electrode slurry, surface treatment of the Li-doped silicon materials has been carried out, but although improvements have been made in the aqueous negative electrode slurry, the stability is still insufficient.
[0015] The present invention has been made in view of the above-mentioned problems, and aims to provide a negative electrode active material for a non-aqueous electrolyte secondary battery that can stabilize an aqueous negative electrode slurry prepared during the preparation of a negative electrode of a secondary battery and can improve initial charge-discharge characteristics when used as a negative electrode active material for a secondary battery. Another aim is to provide a method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery that can stabilize a slurry prepared during the preparation of a negative electrode and can improve initial charge-discharge characteristics. [Means for solving the problem]
[0016] In order to solve the above problems, the present invention provides a negative electrode active material for a non-aqueous electrolyte secondary battery, comprising negative electrode active material particles, the negative electrode active material particles being a silicon compound (SiO x The negative electrode active material particles contain a silicon compound particle containing a Li compound, and at least a part of the surface of the negative electrode active material particle is coated with a carbon material, and the carbon material has a peak derived from the G band by Raman spectroscopy at 1530 cm -1 ~1590cm -1 the amount of the carbon material coated is more than 0.5 mass % and not more than 10 mass % based on the total mass of the silicon compound particles and the carbon material, and a part or the whole of the carbon material is diamond-like carbon.
[0017] The negative electrode active material of the present invention has a high battery capacity because it contains negative electrode active material particles containing a silicon compound. In addition, the SiO 2 in the silicon compound becomes unstable when lithium is inserted and removed during charging and discharging of the battery. 2 Since the component part is modified to another Li compound in advance, it is possible to reduce the irreversible capacity that occurs during charging. In addition, the peak due to the G band in Raman spectroscopy analysis is 1530 cm -1 ~1590cm -1Since the carbon coating is contained, the silicon compound has a suitable conductivity and can improve the capacity retention rate and initial efficiency. Since the G-band peak is in the above range, the silicon compound can be coated with a good carbon coating, and the silicon compound can be stabilized in pure water. The peak due to the G-band is at 1530 cm -1 When the carbon coating is less than 1590 cm, the carbon coating becomes amorphous, which means that the carbon coating cannot be stabilized in pure water and can cause gas generation. -1 If the content exceeds 10%, the crystallization of the bulk silicon-based compound proceeds, resulting in deterioration of the battery characteristics. Furthermore, by having a carbon coating layer of more than 0.5% by mass and not more than 10% by mass, a high-capacity negative electrode active material can be obtained without impairing the capacity of the silicon compound, and the material surface can be coated without impairing the capacity of the silicon-based compound, and the stability in water is also improved. In addition, since the surface of the silicon compound is coated with diamond-like carbon, the amount of gas generation can be suppressed even when the silicon compound is dispersed in pure water, which is a harsher condition than in an aqueous slurry. By coating the surface of the silicon compound with carbon, which is a diamond-like structure made of sp3 carbon, it is possible to suppress dissolution from the inside of the bulk into water and penetration from water into the bulk surface. This improves the stability in the aqueous slurry, and as a result, the battery characteristics can be improved. In the following, the negative electrode active material particles containing silicon compound particles are also referred to as silicon-based active material particles. Moreover, the negative electrode active material containing the silicon-based active material particles is also referred to as a silicon-based active material.
[0018] In this case, it is preferable that the ratios of a G-band peak intensity IG, which is the intensity of a peak derived from a G band, a D-band peak intensity ID, which is the intensity of a peak derived from a D band, and a peak intensity IB at the midpoint between the G-band peak and the D-band peak, in Raman spectroscopy of the negative electrode active material particles, are 1≦ID / IB≦2 and 1≦IG / IB≦2.
[0019] If ID / IB and IG / IB are within the above ranges, it can be determined more reliably from the chart obtained by Raman spectroscopic analysis that the coating carbon component has a diamond-like structure.
[0020] In addition, it is preferable that the intensity ratio ID / IG of a D-band peak intensity ID, which is the intensity of a peak derived from a D band, and a G-band peak intensity IG, which is the intensity of a peak derived from a G band, in Raman spectroscopy of the negative electrode active material particles is 0≦ID / IG≦1.5.
[0021] In this way, if 0≦ID / IG≦1.5, peeling of the carbon film due to expansion and contraction and side reactions on the carbon surface can be suppressed, resulting in better battery characteristics.
[0022] In addition, it is preferable that the intensity ratio ISi / IG of the Si peak intensity ISi, which is the intensity of the peak derived from Si, and the G band peak intensity IG, which is the intensity of the peak derived from the G band, in Raman spectroscopy of the negative electrode active material particles, is 0≦ISi / IG≦2.0.
[0023] In this way, when 0≦ISi / IG≦2.0, it is possible to suppress surface exposure of the silicon-based compound particles while delaying gas generation in water, resulting in better battery characteristics.
[0024] The negative electrode active material particles have a true density of 2.0 to 2.5 g / cm 3 It is preferable that:
[0025] The true density of the negative electrode active material particles coated with carbon in this way is 2 to 2.5 g / cm 3 In this case, the surface is coated with a carbon material of appropriate density, which provides stability in water and allows the battery to adapt to expansion and contraction during charging and discharging, resulting in good battery characteristics.
[0026] In addition, the true density of the carbon material of the negative electrode active material particles is 1.4 to 1.9 g / cm 3 It is preferable that:
[0027] A carbon film with such a density is stable in water and can follow the expansion and contraction of the silicon compound during charging and discharging, resulting in good battery characteristics.
[0028] Moreover, the negative electrode active material particles preferably have an adsorption / desorption isotherm, obtained by nitrogen gas adsorption / desorption isotherm measurement, that exhibits characteristics of type II or III in the IUPAC classification.
[0029] In this way, when the negative electrode active material particles are classified as type II or type III according to the IUPAC classification when the adsorption / desorption isotherm is measured, there are no pores on the surface, or even if there are, they are minute macropores, and the silicon compound particles are evenly coated without unevenness, so that the elution of components from inside the bulk can be suppressed. In addition, the surface reaction of the material during charging and discharging can be suppressed, which results in improved battery characteristics.
[0030] The negative electrode active material particles have a specific surface area of 0.5 m 2 / g or more 5.0m 2 It is preferable that the molecular weight is not more than 1 / g.
[0031] In this way, the specific surface area of the negative electrode active material particles is 0.5 m 2 / g or more 5.0m 2 / g or less, the reaction area in water is limited, improving stability. The same is true when used in a battery, where the surface reaction is limited during charging and discharging, resulting in improved battery characteristics.
[0032] In addition, the Li 2 SiO 3 The half-width of the peak attributable to the peak near 2θ=18.7° is preferably 0.5° or more and 3.0° or less.
[0033] In this way, the Li 2 SiO 3When the half-width of the peak attributable to the peak near 2θ=18.7° is 0.5° or more and 3.0° or less, the elution of alkaline components into the aqueous slurry can be suppressed, and better battery characteristics can be obtained.
[0034] Furthermore, it is preferable that the crystallite size resulting from the Si(220) crystal plane obtained by X-ray diffraction of the negative electrode active material is 1 nm or more and 5 nm or less.
[0035] In this way, if the crystallite size resulting from the Si(220) crystal plane of the negative electrode active material is within the above range, better battery characteristics can be obtained.
[0036] The silicon compound particles preferably have a median diameter of 0.5 μm or more and 20 μm or less.
[0037] In this way, if the median diameter of the silicon compound particles is 0.5 μm or more, the area on the surface of the silicon compound particles where side reactions occur is small, so that Li is not consumed excessively and the cycle retention rate of the battery can be maintained high. Also, if the median diameter is 20 μm or less, the expansion when Li is inserted is small, so that the battery is less likely to break and is less likely to crack. Furthermore, since the expansion of the silicon compound particles is small, for example, a negative electrode active material layer in which a carbon active material is mixed with a commonly used silicon-based active material is less likely to be destroyed.
[0038] In order to achieve the above object, the present invention also provides a non-aqueous electrolyte secondary battery comprising any one of the above negative electrode active materials for non-aqueous electrolyte secondary batteries.
[0039] Such a secondary battery has a high cycle retention rate and initial efficiency, and can be advantageously produced industrially.
[0040] The present invention also provides a mobile terminal including the above nonaqueous electrolyte secondary battery.
[0041] The present invention also provides an electric power vehicle equipped with the above nonaqueous electrolyte secondary battery.
[0042] The present invention also provides a power storage system including the above nonaqueous electrolyte secondary battery.
[0043] The mobile terminal, electric power vehicle, and power storage system including the nonaqueous electrolyte secondary battery are preferable because the nonaqueous electrolyte secondary battery has a high battery capacity, and has good cycle characteristics and initial efficiency.
[0044] In order to achieve the above object, the present invention provides a silicon compound (SiO x a step of preparing silicon compound particles containing a carbon material having a molecular weight of 0.5≦x≦1.6), a step of coating at least a portion of the silicon compound particles with a carbon material, and a step of inserting Li into the silicon compound particles to prepare negative electrode active material particles for use in a non-aqueous electrolyte secondary battery, the step of preparing a negative electrode active material using the silicon compound particles, the step of preparing a negative electrode active material using the negative electrode active material particles, the step of adjusting the amount of the carbon material coating to be more than 0.5% by mass and not more than 10% by mass with respect to the total mass of the silicon compound particles and the carbon material in the negative electrode active material particles to be prepared, and the coating of the carbon material is adjusted so that a peak derived from the G band in Raman spectroscopy of the carbon material in the negative electrode active material particles to be prepared is 1530 cm -1 ~1590cm -1 and a method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery, the method being characterized in that the carbon material is partially or entirely converted into diamond-like carbon.
[0045] Such a method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery can provide a non-aqueous negative electrode active material that takes advantage of the inherent properties of silicon oxide modified with Li and has a high battery capacity and a good cycle retention rate. Effect of the Invention
[0046] The negative electrode active material for non-aqueous electrolyte secondary batteries of the present invention can form an industrially usable coating film, and therefore can substantially improve the battery capacity, cycle characteristics, and initial charge / discharge characteristics. In particular, the surface of the silicon compound is covered with carbon, which is a diamond-like structure made of sp3 carbon, and can suppress dissolution from the inside of the bulk into water and penetration from water into the bulk surface. This improves stability in aqueous slurry, and as a result, can improve battery characteristics. In addition, the secondary battery of the present invention containing this negative electrode active material can be produced industrially with advantage, and has good battery capacity, cycle characteristics, and initial charge / discharge characteristics. In addition, the same effect can be obtained in electronic devices, power tools, electric vehicles, power storage systems, and the like using the secondary battery of the present invention.
[0047] Moreover, the method for producing a negative electrode active material for a nonaqueous electrolyte secondary battery of the present invention can produce a negative electrode active material that can improve the stability of a slurry prepared during the production of a secondary battery and can also improve the battery capacity, cycle characteristics, and initial charge / discharge characteristics. [Brief description of the drawings]
[0048] [Figure 1] 1 is a cross-sectional view showing the configuration of a negative electrode containing a negative electrode active material of the present invention. [Diagram 2] 1 is an in-bulk reforming apparatus that can be used when producing the negative electrode active material of the present invention. [Diagram 3] FIG. 1 is an exploded view showing a configuration example (laminate film type) of a lithium ion secondary battery including the negative electrode active material of the present invention. [Figure 4] FIG. 2 is a chart showing a Raman spectroscopic analysis of the negative electrode active material of the present invention. [Diagram 5] FIG. 2 is a plot diagram for determining the density of the coated carbon material of the negative electrode active material of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0049] Hereinafter, the present invention will be described in detail with reference to the preferred embodiments, but the present invention is not limited thereto.
[0050] As mentioned above, as one method for increasing the battery capacity of lithium-ion secondary batteries, the use of a negative electrode mainly made of silicon-based active material as the negative electrode of lithium-ion secondary batteries has been considered. Lithium-ion secondary batteries mainly made of silicon-based active material are expected to have initial efficiency and cycle characteristics similar to those of lithium-ion secondary batteries using carbon materials, but no negative electrode active material has been proposed that shows cycle stability equivalent to that of non-aqueous electrolyte secondary batteries using carbon materials. In particular, silicon compounds containing oxygen have a lower initial efficiency than carbon materials, so the improvement in battery capacity has been limited.
[0051] Therefore, the present inventors conducted extensive research in order to obtain a negative electrode active material that enables easy production of a nonaqueous electrolyte secondary battery that has a high battery capacity as well as good cycle characteristics and initial efficiency, and have arrived at the present invention.
[0052] [Negative Electrode Active Material for Non-Aqueous Electrolyte Secondary Battery of the Present Invention] The negative electrode active material of the present invention contains negative electrode active material particles, and the negative electrode active material particles are made of a silicon compound (SiO x The negative electrode active material particles contain silicon compound particles containing a Li compound. The silicon compound particles contain a Li compound. Furthermore, at least a part of the surface of the negative electrode active material particles is covered with a carbon material. Furthermore, the carbon material has a peak at 1530 cm due to the G band by Raman spectroscopy. -1 ~1590cm -1 Furthermore, the amount of the carbon material coated is more than 0.5 mass % and 10 mass % or less with respect to the total mass of the silicon compound particles and the carbon material, and a part or the whole of the carbon material is diamond-like carbon.
[0053] Such a negative electrode active material has a high battery capacity because it contains negative electrode active material particles containing a silicon compound. In addition, the SiO in the silicon compound becomes unstable when lithium is inserted and removed during charging and discharging of the battery. 2Since the component part has been modified to another Li compound in advance, it is possible to reduce the irreversible capacity that occurs during charging. -1 ~1590cm -1 Since the carbon coating layer is more than 0.5 mass % and 10 mass % or less, the negative electrode active material has a moderate electrical conductivity and can improve the capacity retention rate and initial efficiency. Furthermore, since the carbon coating layer is more than 0.5 mass % and 10 mass % or less, a high-capacity negative electrode active material can be obtained without impairing the capacity of the silicon compound. In addition, since the surface of the silicon compound is coated with diamond-like carbon, the amount of gas generation can be suppressed even when the silicon compound is dispersed in pure water, which is a harsher condition than in an aqueous slurry. The stability in an aqueous slurry is also improved, and as a result, the battery characteristics can be improved.
[0054] A chart of Raman spectroscopy of the negative electrode active material of the present invention is shown in Fig. 4. As shown in Fig. 4, the negative electrode active material of the present invention has a peak derived from the G band (G band peak) at 1530 cm -1 ~1590cm -1 The G band peak in the Raman spectroscopy of carbon shifts to 1530 cm -1 ~1590cm -1 However, the negative electrode active material of the present invention has a G band peak in the above range. -1 When the carbon coating is less than 1590 cm, the carbon coating becomes amorphous, which means that the carbon coating cannot be stabilized in pure water and can cause gas generation. -1 If the temperature exceeds this range, crystallization of the bulk silicon-based compound proceeds, resulting in deterioration of the battery characteristics.
[0055] In addition, the negative electrode active material particles of the present invention preferably have a ratio of the G-band peak intensity IG, which is the intensity of the peak derived from the G-band, the D-band peak intensity ID, which is the intensity of the peak derived from the D-band, and the peak intensity IB at the midpoint between the G-band peak and the D-band peak, of 1≦ID / IB≦2 and 1≦IG / IB≦2. If ID / IB and IG / IB are within the above ranges, it can be more reliably determined from the chart obtained by Raman spectroscopy that the coating carbon component has a diamond-like structure. In addition, in the negative electrode active material particles of the present invention, the G-band peak is at 1530 to 1590 cm -1 The wavenumber at which the maximum peak is located within the range of 1330 to 1370 cm -1 The wavenumber at which the maximum peak is located and the wavenumber for calculating the peak intensity IB is the midpoint (average of both wavenumbers) between the wavenumber of the G band peak and the wavenumber of the D band peak.
[0056] In addition, the negative electrode active material particles of the present invention preferably have an intensity ratio ID / IG of the D-band peak intensity ID, which is the intensity of the peak derived from the D-band by Raman spectroscopy, to the G-band peak intensity IG, which is the intensity of the peak derived from the G-band, of 0≦ID / IG≦1.5. If 0≦ID / IG≦1.5, peeling of the carbon film due to expansion and contraction and side reactions on the carbon surface can be suppressed, thereby obtaining better battery characteristics.
[0057] In addition, the negative electrode active material particles of the present invention preferably have an intensity ratio ISi / IG of the Si peak intensity ISi, which is the intensity of the peak derived from Si, and the G band peak intensity IG, which is the intensity of the peak derived from the G band, of 0≦ISi / IG≦2.0. If 0≦ISi / IG≦2.0, the surface exposure of the silicon-based compound particles can be suppressed while gas generation in water can be delayed, resulting in better battery characteristics.
[0058] The negative electrode active material particles of the present invention have a true density of the whole particle of 2.0 to 2.5 g / cm 3It is preferable that the true density of the negative electrode active material particles thus coated with carbon is 2 to 2.5 g / cm. 3 In this case, the surface is coated with a carbon material of appropriate density, which provides stability in water and allows the battery to adapt to expansion and contraction during charging and discharging, resulting in good battery characteristics.
[0059] In addition, the negative electrode active material particles of the present invention have a true density of the carbon material of 1.4 to 1.9 g / cm 3 It is preferable that the density of the carbon film is such that the carbon film has stability in water and can follow the expansion and contraction of the silicon compound during charging and discharging, resulting in good battery characteristics. The density of the carbon material (carbon coating) can be determined, for example, as shown in FIG. 5, by plotting the content (mass%) of the carbon material relative to the total amount of the silicon compound and the carbon material and the density of the particles made of the silicon compound and the carbon material (carbon coating) at several points, extrapolating the point where the content of the carbon material is 100 mass% by linear approximation, and calculating the density of the carbon material alone.
[0060] In addition, the negative electrode active material particles of the present invention preferably have the characteristics of type II or type III in the IUPAC classification in the adsorption and desorption isotherm obtained by measuring the adsorption and desorption isotherm with nitrogen gas. Thus, when the negative electrode active material particles are measured for the adsorption and desorption isotherm, if they are type II or type III in the IUPAC classification, there are no pores on the surface, or even if they are present, they are minute macropores, and the silicon compound particles can be uniformly coated without unevenness, so that the elution of components from the inside of the bulk can be suppressed. In addition, the surface reaction of the material during charging and discharging can be suppressed, which results in improved battery characteristics.
[0061] The negative electrode active material particles of the present invention have a specific surface area of 0.5 m 2 / g or more 5.0m 2 The specific surface area of the negative electrode active material particles of the present invention can be determined by the BET method. 2 / g or more 5.0m 2 / g or less, the reaction area in water is limited, improving stability. The same is true when used in a battery, where the surface reaction is limited during charging and discharging, resulting in improved battery characteristics.
[0062] In addition, the negative electrode active material particles of the present invention contain Li as the Li compound. 2 SiO 3 The Li 2 SiO 3 It is preferable that the half-width of the peak at 2θ=18.7° due to the peak is 0.5° or more and 3.0° or less. 2 SiO 3 When the half-width of the peak attributable to the peak near 2θ=18.7° is 0.5° or more and 3.0° or less, the elution of alkaline components into the aqueous slurry can be suppressed, and better battery characteristics can be obtained.
[0063] As described above, the negative electrode active material of the present invention is SiO x (0.5≦x≦1.6). The silicon-based active material particles are made of silicon oxide material (SiO x (0.5≦x≦1.6), and it is preferable that x is close to 1 in the composition. This is because high cycle characteristics can be obtained. Note that the composition of the silicon oxide material in the present invention does not necessarily mean 100% purity, and may contain trace amounts of impurity elements and Li.
[0064] In the present invention, the lower the crystallinity of the silicon compound, the better. Specifically, it is desirable that the crystallite size resulting from the Si(220) crystal plane obtained by X-ray diffraction of the negative electrode active material (silicon-based active material) is 1 nm or more and 5 nm or less. In particular, it is preferable that the diffraction peak is broad and has no clear peak. In this way, by having particularly low crystallinity and a small amount of Si crystals, not only can the battery characteristics be improved, but also a stable Li compound can be generated.
[0065] The crystallite size due to the (220) crystal plane can be calculated by XRD peak analysis. Calculation of the crystallite size by XRD can be performed, for example, under the following conditions. For broad peaks, analysis software TOPAS can be used, for example, under the following conditions. XRD measurement Equipment: Bruker D2 PHASER ·X-ray source:Cu Divergence slit: 0.5° ·Inlet side solar: 4° - Receiving side solar: 4° Calculation of crystallite size Analysis software: DIFFRAC.TOPAS Analysis method: Peak fitting method Emission Profile: CuKa5.lam Function: FP (First Principle) function Refinement Option: Select “Calculate Error” and “Use Extrapolation”
[0066] In addition, the median diameter of the silicon compound particles is not particularly limited, but is preferably 0.5 μm or more and 20 μm or less. This is because in this range, lithium ions are easily absorbed and released during charging and discharging, and the silicon-based active material particles are less likely to break. If the median diameter is 0.5 μm or more, the surface area is not too large, so side reactions are less likely to occur during charging and discharging, and the irreversible capacity of the battery can be reduced. On the other hand, if the median diameter is 20 μm or less, the silicon-based active material particles are less likely to break and new surfaces are less likely to appear, which is preferable. In the description of the present invention, the median diameter is the cumulative average diameter D in the volume-based particle size distribution measured by the laser diffraction scattering method. 50 means...
[0067] Furthermore, in the present invention, the silicon-based active material contains Li as the Li compound contained in the silicon compound as described above. 2 SiO 3 It is preferable that the compound contains Li4 SiO 4 , Li 6 S 2 O 7 , Li 2 SiO 3 Li 4 SiO 4 , Li 6 S 2 O 7 , Li 2 SiO 3 Li silicates such as these are relatively more stable than other Li compounds, so silicon-based active materials containing these Li compounds can provide more stable battery characteristics. These Li compounds are formed inside the silicon compounds by the SiO 2 It can be obtained by selectively changing part of the components to Li compounds and modifying silicon compounds.
[0068] The amount of Li compound in the silicon compound can be quantified by NMR (nuclear magnetic resonance). NMR measurement can be performed, for example, under the following conditions. 29 Si MAS NMR (Magic Angle Spinning Nuclear Magnetic Resonance) Equipment: Bruker 700 NMR spectrometer; Probe: 4mm HR-MAS rotor 50μL, Sample rotation speed: 10kHz, ·Measurement environment temperature: 25℃
[0069] In addition, in the present invention, when modifying the silicon compound, electrochemical methods, modification by oxidation-reduction reaction, and physical methods such as thermal doping can be used. In particular, when the silicon compound is modified using electrochemical methods and modification by oxidation-reduction, the battery characteristics of the negative electrode active material are improved. In addition, in the modification, not only the insertion of Li into the silicon compound but also the stabilization of the Li compound by heat treatment and the desorption of Li from the silicon compound are preferably performed at the same time. This further improves the stability of the negative electrode active material against the slurry, such as its water resistance.
[0070] As described above, in the present invention, the silicon compound in the silicon-based active material particles contains a carbon coating on at least a portion of the surface, so that appropriate electrical conductivity can be obtained.
[0071] <Non-aqueous electrolyte secondary battery negative electrode> Next, the configuration of a negative electrode for a non-aqueous electrolyte secondary battery (hereinafter also referred to as "negative electrode") containing the negative electrode active material of the present invention will be described.
[0072] [Negative electrode composition] Fig. 1 shows a cross-sectional view of a negative electrode including the negative electrode active material of the present invention. As shown in Fig. 1, a negative electrode 10 has a negative electrode active material layer 12 on a negative electrode current collector 11. This negative electrode active material layer 12 may be provided on both sides or only one side of the negative electrode current collector 11. Furthermore, the negative electrode of the nonaqueous electrolyte secondary battery of the present invention does not necessarily need to have the negative electrode current collector 11.
[0073] [Negative electrode current collector] The negative electrode current collector 11 is made of a material having excellent electrical conductivity and excellent mechanical strength. Examples of the conductive material that can be used for the negative electrode current collector 11 include copper (Cu) and nickel (Ni). It is preferable that this conductive material does not form an intermetallic compound with lithium (Li).
[0074] The negative electrode current collector 11 preferably contains carbon (C) and / or sulfur (S) in addition to the main elements. This is because the physical strength of the negative electrode current collector is improved. In particular, when the current collector has an active material layer that expands during charging, if the current collector contains the above elements, this has the effect of suppressing deformation of the electrode including the current collector. The content of the above contained elements is not particularly limited, but is preferably 100 ppm or less. This is because a higher deformation suppression effect can be obtained.
[0075] The surface of the negative electrode current collector 11 may be roughened or may not be roughened. The roughened negative electrode current collector is, for example, a metal foil that has been electrolytically treated, embossed, or chemically etched. The unroughened negative electrode current collector is, for example, a rolled metal foil.
[0076] [Negative electrode active material layer] The negative electrode active material layer 12 may contain a plurality of types of negative electrode active materials such as a carbon-based active material in addition to silicon-based active material particles. Furthermore, in terms of battery design, it may contain other materials such as a thickener (also called a "binding agent" or "binder") and a conductive assistant.
[0077] [Method of manufacturing negative electrode active material and negative electrode] Next, an example of a method for producing the negative electrode active material and the negative electrode of the nonaqueous electrolyte secondary battery of the present invention will be described.
[0078] First, a method for producing the negative electrode active material contained in the negative electrode will be described. The method for producing the negative electrode active material for a non-aqueous electrolyte secondary battery of the present invention is to use a silicon compound (SiO x a step of preparing silicon compound particles containing a carbon material having a molecular weight of 0.5≦x≦1.6), a step of coating at least a portion of the silicon compound particles with a carbon material, and a step of inserting Li into the silicon compound particles to prepare negative electrode active material particles for use in a non-aqueous electrolyte secondary battery, the step of preparing a negative electrode active material using the silicon compound particles, the step of preparing a negative electrode active material using the negative electrode active material particles, the step of adjusting the amount of the carbon material coating to be more than 0.5% by mass and not more than 10% by mass with respect to the total mass of the silicon compound particles and the carbon material in the negative electrode active material particles to be prepared, and the coating of the carbon material is adjusted so that a peak derived from the G band in Raman spectroscopy of the carbon material in the negative electrode active material particles to be prepared is 1530 cm -1 ~1590cm -1 and characterized in that the process is carried out under conditions in which a part or all of the carbon material becomes diamond-like carbon.
[0079] In other words, first, SiO xSilicon compound particles (silicon oxide particles) represented by (0.5≦x≦1.6) are prepared. Next, a carbon coating is formed on the surface of the silicon oxide particles. Next, Li is inserted into and removed from the silicon oxide particles to modify the silicon oxide particles. At this time, Li compounds can be generated inside or on the surface of the silicon oxide particles at the same time. In addition, either the formation of the carbon coating or the insertion of Li into the silicon compound particles can be performed first. In any case, the coating of the carbon material is performed under the conditions that the amount of the carbon material coated is as described above, the position of the peak derived from the G band in Raman spectroscopy of the carbon material is within the above range, and part or all of the carbon material becomes diamond-like carbon. Such conditions depend on the actual device for performing the carbon coating, but can be easily determined by experiment. Thereafter, for example, the modified silicon compound particles are washed with an alkaline water having dissolved therein alcohol or lithium carbonate, a weak acid, or pure water, and the like, and then the silicon compound particles are used as negative electrode active material particles, and mixed with a conductive assistant and a binder, thereby producing a negative electrode active material and a negative electrode.
[0080] More specifically, the negative electrode active material is produced, for example, by the following procedure.
[0081] First, the raw material that generates silicon oxide gas is heated in the presence of an inert gas or under reduced pressure at a temperature range of 900°C to 1600°C to generate silicon oxide gas. In this case, the raw material is a mixture of metal silicon powder and silicon dioxide powder, and considering the surface oxygen of the metal silicon powder and the presence of trace oxygen in the reactor, the mixed molar ratio is preferably in the range of 0.8<metal silicon powder / silicon dioxide powder<1.3. The Si crystallites in the particles are controlled by changing the feeding range and vaporization temperature, and by heat treatment after generation. The generated gas is deposited on an adsorption plate. The temperature inside the reactor is lowered to below 100°C, and the deposit is taken out and crushed and powdered using a ball mill, jet mill, etc.
[0082] Next, Li is inserted into the negative electrode active material particles containing the silicon active material particles prepared as described above to contain a Li compound. 2 SiO 3, Li 6 S 2 O 7 , Li 4 SiO 4 It is preferable to contain at least one of the following: The insertion of Li is preferably carried out by an electrochemical method or an oxidation-reduction method.
[0083] In the electrochemical reforming, the structure of the apparatus is not particularly limited, but for example, the in-bulk reforming can be performed using a Li-doped reforming apparatus (in-bulk reforming apparatus) 20 shown in FIG. 2. The in-bulk reforming apparatus 20 has a bath 27 filled with an organic solvent 23, a positive electrode (lithium source, reforming source) 21 arranged in the bath 27 and connected to one side of a power supply 26, a powder storage container 25 arranged in the bath 27 and connected to the other side of the power supply 26, and a separator 24 provided between the positive electrode 21 and the powder storage container 25. The powder storage container 25 stores silicon oxide powder 22. The powder storage container stores a silicon compound (silicon oxide particles), and a voltage is applied from the power source to the powder storage container storing the silicon oxide particles and the positive electrode (lithium source). This allows lithium to be inserted into and removed from the silicon compound particles, so that the silicon oxide powder 22 can be reformed. By subjecting the obtained silicon oxide to a heat treatment at 400 to 800° C., the Li compound can be stabilized.
[0084] As the organic solvent 23 in the bath 27, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, etc. can be used. In addition, as the electrolyte salt contained in the organic solvent 23, lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ) etc. can be used.
[0085] The positive electrode 21 may be a Li foil or a Li-containing compound such as lithium carbonate, lithium oxide, lithium cobalt oxide, lithium iron olivine, lithium nickel oxide, or lithium vanadium phosphate.
[0086] After electrochemical Li-doping, the slurry may be washed with alkaline water containing lithium carbonate, lithium oxide, or lithium hydroxide dissolved therein, alcohol, weak acid, or pure water. By washing, the excess alkaline components can be dissolved out, improving the slurry stability.
[0087] In the modification by the oxidation-reduction method, for example, first, lithium can be inserted by immersing silicon active material particles in solution A in which lithium is dissolved in an ether-based solvent. This solution A may further contain a polycyclic aromatic compound or a linear polyphenylene compound. The Li compound can be stabilized by heat-treating the obtained silicon oxide at 400 to 800 ° C. In addition, after lithium insertion, active lithium can be desorbed from the silicon active material particles by immersing the silicon active material particles in solution B containing a polycyclic aromatic compound or a linear polyphenylene compound or a derivative thereof. The solvent for this solution B can be, for example, an ether-based solvent, a ketone-based solvent, an ester-based solvent, an alcohol-based solvent, an amine-based solvent, or a mixture thereof. The silicon active material may be washed with alkaline water, alcohol, weak acid, or pure water in which lithium carbonate, lithium oxide, or lithium hydroxide is dissolved. By washing, excess alkaline components can be eluted, and the slurry stability is improved. As described above, a carbon film may be formed on the surface of the powder material obtained after lithium insertion (or before lithium insertion as described above). The carbon film is effective in further improving the battery characteristics of the negative electrode active material.
[0088] Pyrolytic CVD is a preferred method for forming a carbon coating on the surface of a powder material. In pyrolytic CVD, silicon oxide powder is placed in a furnace, which is filled with hydrocarbon gas to raise the temperature inside the furnace. There are no particular limitations on the decomposition temperature, but it is particularly preferred to set it at 1000°C or lower. A temperature of 850°C or lower is even more preferred, as this makes it possible to suppress unintended disproportionation of silicon oxide. There are no particular limitations on the hydrocarbon gas, but it is preferred to set it at 1000°C or lower. n H m Among the compositions, 3≧n is preferred because this leads to low production costs and good physical properties of the decomposition products.
[0089] As the ether solvent used in solution A, diethyl ether, tert-butyl methyl ether, tetrahydrofuran, dioxane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, or a mixture thereof can be used. Among these, it is particularly preferable to use tetrahydrofuran, dioxane, 1,2-dimethoxyethane, or diethylene glycol dimethyl ether. These solvents are preferably dehydrated and deoxygenated.
[0090] The polycyclic aromatic compound contained in solution A may be one or more of naphthalene, anthracene, phenanthrene, naphthalene, pentacene, pyrene, triphenylene, coronene, chrysene, and derivatives thereof, and the linear polyphenylene compound may be one or more of biphenyl, terphenyl, and derivatives thereof.
[0091] The polycyclic aromatic compound contained in solution B may be one or more of naphthalene, anthracene, phenanthrene, naphthalene, pentacene, pyrene, triphenylene, coronene, chrysene, and derivatives thereof.
[0092] As the ether solvent for solution B, diethyl ether, tert-butyl methyl ether, tetrahydrofuran, dioxane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, or a mixture of these solvents can be used.
[0093] As the ketone solvent, acetone, acetophenone, etc. can be used.
[0094] As the ester solvent, methyl formate, methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, and the like can be used.
[0095] As the alcohol-based solvent, methanol, ethanol, propanol, isopropyl alcohol, and the like can be used.
[0096] As the amine solvent, methylamine, ethylamine, ethylenediamine, and the like can be used.
[0097] Li may also be inserted into the negative electrode active material particles by thermal doping. In this case, for example, the negative electrode active material particles may be mixed with LiH powder or Li powder and heated under a non-oxidizing atmosphere to modify the material. For example, an Ar atmosphere may be used as the non-oxidizing atmosphere. More specifically, LiH powder or Li powder and silicon oxide powder are thoroughly mixed under an Ar atmosphere, sealed, and homogenized by stirring the sealed container. Then, the material is heated in the range of 700°C to 750°C to modify the material. In this case, in order to remove Li from the silicon compound, the powder after heating may be thoroughly cooled and washed with alkaline water, alcohol, weak acid, or pure water in which lithium carbonate, lithium oxide, or lithium hydroxide is dissolved. By washing, excess alkaline components can be eluted, improving the slurry stability.
[0098] <Lithium-ion secondary battery> Next, a laminate film type lithium ion secondary battery will be described as a specific example of the nonaqueous electrolyte secondary battery of the present invention.
[0099] [Configuration of laminated film type secondary battery] The laminated film type lithium ion secondary battery 30 shown in FIG. 3 is a battery in which a wound electrode body 31 is housed inside a sheet-like exterior member 35. This wound electrode body 31 has a separator between the positive electrode and the negative electrode, and is wound. There are also cases where a separator is between the positive electrode and the negative electrode and a laminate is housed. In either electrode body, a positive electrode lead 32 is attached to the positive electrode, and a negative electrode lead 33 is attached to the negative electrode. The outermost periphery of the electrode body is protected by a protective tape.
[0100] The positive and negative electrode leads 32, 33 are led out in one direction, for example, from the inside to the outside of the exterior member 35. The positive electrode lead 32 is formed of a conductive material such as aluminum, and the negative electrode lead 33 is formed of a conductive material such as nickel or copper.
[0101] The exterior member 35 is, for example, a laminate film in which a fusion layer, a metal layer, and a surface protection layer are laminated in this order, and the outer peripheral edges of the fusion layers of the two films of this laminate film are fused together or pasted together with an adhesive so that the fusion layer faces the electrode body 31. The fusion part is, for example, a film such as polyethylene or polypropylene, and the metal part is aluminum foil, etc. The protection layer is, for example, nylon, etc.
[0102] An adhesive film 34 is inserted between the exterior member 35 and the positive and negative electrode leads to prevent outside air from entering. The material for this is, for example, polyethylene, polypropylene, or polyolefin resin.
[0103] The positive electrode has a positive electrode active material layer on either or both sides of a positive electrode current collector, similar to the negative electrode 10 in FIG.
[0104] The positive electrode current collector is made of a conductive material such as aluminum.
[0105] The positive electrode active material layer contains one or more positive electrode materials capable of absorbing and releasing lithium ions, and may contain other materials such as a positive electrode binder, a positive electrode conductive assistant, a dispersant, etc., depending on the design. In this case, details regarding the positive electrode binder and the positive electrode conductive assistant are the same as, for example, the negative electrode binder and the negative electrode conductive assistant already described.
[0106] As the positive electrode material, a lithium-containing compound is desirable. Examples of such lithium-containing compounds include composite oxides composed of lithium and transition metal elements, or phosphate compounds containing lithium and transition metal elements. Among these positive electrode materials, compounds containing at least one of nickel, iron, manganese, and cobalt are preferred. Their chemical formulas are, for example, Li x M 1 O 2 or Li y M 2 PO 4 . In the formula, M 1 , M 2 represent at least one transition metal element. The values of x and y vary depending on the charge and discharge state of the battery, but generally are represented by 0.05 ≦ x ≦ 1.10, 0.05 ≦ y ≦ 1.10.
[0107] Examples of the composite oxide containing lithium and transition metal elements include lithium cobalt composite oxide (Li x CoO 2 ), lithium nickel composite oxide (Li x NiO 2 ), and lithium nickel cobalt composite oxide. Examples of the lithium nickel cobalt composite oxide include lithium nickel cobalt aluminum composite oxide (NCA) and lithium nickel cobalt manganese composite oxide (NCM).
[0108] Examples of the phosphate compound containing lithium and transition metal elements include lithium iron phosphate compound (LiFePO 4 ) or lithium iron manganese phosphate compound (LiFe 1-u Mn u PO 4 (0 < u < 1), etc. By using these positive electrode materials, a high battery capacity can be obtained, and excellent cycle characteristics can also be obtained.
[0109] [Negative electrode] The negative electrode has the same structure as the negative electrode 10 for lithium ion secondary battery shown in Fig. 1, and has, for example, a negative electrode active material layer on both sides of a current collector. It is preferable that this negative electrode has a negative electrode charge capacity larger than the electric capacity (charge capacity as a battery) obtained from the positive electrode active material. This makes it possible to suppress the deposition of lithium metal on the negative electrode.
[0110] The positive electrode active material layer is provided on a part of both sides of the positive electrode current collector, and similarly, the negative electrode active material layer is provided on a part of both sides of the negative electrode current collector. In this case, for example, the negative electrode active material layer provided on the negative electrode current collector has a region where the opposing positive electrode active material layer is not present. This is for the purpose of designing a stable battery.
[0111] The region where the negative electrode active material layer and the positive electrode active material layer do not face each other is hardly affected by charging and discharging, so the state of the negative electrode active material layer is maintained as it is immediately after formation, and the composition of the negative electrode active material can be accurately examined with good reproducibility regardless of the presence or absence of charging and discharging.
[0112] [Separator] The separator separates the positive electrode from the negative electrode, prevents current short circuit caused by contact between the electrodes, and allows lithium ions to pass through. The separator is formed of a porous film made of, for example, synthetic resin or ceramic, and may have a laminated structure in which two or more types of porous films are laminated. Examples of synthetic resins include polytetrafluoroethylene, polypropylene, and polyethylene.
[0113] [Electrolyte] At least a portion of the active material layer or the separator is impregnated with a liquid electrolyte (electrolytic solution). This electrolytic solution contains an electrolyte salt dissolved in a solvent, and may contain other materials such as additives.
[0114] The solvent may be, for example, a non-aqueous solvent. Examples of non-aqueous solvents include ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, 1,2-dimethoxyethane, and tetrahydrofuran. Among these, it is desirable to use at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. This is because better characteristics can be obtained. In this case, more advantageous characteristics can be obtained by combining a high-viscosity solvent such as ethylene carbonate or propylene carbonate with a low-viscosity solvent such as dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. This is because the dissociation and ion mobility of the electrolyte salt are improved.
[0115] It is preferable that the solvent additive contains an unsaturated carbon-bonded cyclic carbonate. This is because a stable coating is formed on the negative electrode surface during charging and discharging, and the decomposition reaction of the electrolyte can be suppressed. Examples of the unsaturated carbon-bonded cyclic carbonate include vinylene carbonate and vinylethylene carbonate.
[0116] It is also preferable that the solvent additive contains sultone (cyclic sulfonic acid ester), because this improves the chemical stability of the battery. Examples of sultones include propane sultone and propene sultone.
[0117] Furthermore, it is preferable that the solvent contains an acid anhydride, because this improves the chemical stability of the electrolyte. As the acid anhydride, for example, propane disulfonic acid anhydride can be mentioned.
[0118] The electrolyte salt may include at least one of light metal salts such as lithium salts, for example. Examples of the lithium salt include lithium hexafluorophosphate (LiPF6) and lithium tetrafluoroborate (LiBF4).
[0119] The content of the electrolyte salt is preferably 0.5 mol / kg or more and 2.5 mol / kg or less relative to the solvent, because this provides high ionic conductivity.
[0120] [Manufacturing method of laminate film type secondary battery] First, a positive electrode is prepared using the above-mentioned positive electrode material. First, a positive electrode active material is mixed with a positive electrode binder, a positive electrode conductive assistant, etc., if necessary, to prepare a positive electrode mixture, which is then dispersed in an organic solvent to prepare a positive electrode mixture slurry. Next, the mixture slurry is applied to a positive electrode current collector using a coating device such as a knife roll or a die coater having a die head, and the mixture is dried with hot air to obtain a positive electrode active material layer. Finally, the positive electrode active material layer is compression molded using a roll press machine or the like. At this time, heating may be performed, and compression may be repeated multiple times.
[0121] Next, using the same procedure as in the production of the lithium ion secondary battery negative electrode 10 described above, a negative electrode active material layer is formed on the negative electrode current collector to produce the negative electrode.
[0122] When preparing the positive and negative electrodes, active material layers are formed on both sides of the positive and negative current collectors, respectively. At this time, the lengths of the active material applied on both sides of each electrode may be offset (see FIG. 2).
[0123] Next, the electrolyte is adjusted. Next, the positive electrode lead 32 is attached to the positive electrode current collector by ultrasonic welding or the like, and the negative electrode lead 33 is attached to the negative electrode current collector. Next, the positive electrode and the negative electrode are laminated or wound with a separator interposed therebetween to prepare a wound electrode body 31, and a protective tape is attached to the outermost periphery. Next, the wound body is molded to have a flat shape. Next, the wound electrode body is sandwiched between folded film-like exterior members 35, and then the insulating parts of the exterior members are bonded to each other by a heat fusion method, and the wound electrode body is enclosed in a state in which only one direction is open. Next, an adhesive film is inserted between the positive electrode lead and the negative electrode lead and the exterior member. Next, a predetermined amount of the above-prepared electrolyte is poured from the open portion, and vacuum impregnation is performed. After impregnation, the open portion is bonded by a vacuum heat fusion method. In this manner, a laminate film type secondary battery 30 can be manufactured.
[0124] In the nonaqueous electrolyte secondary battery of the present invention, such as the laminate film type secondary battery 30 prepared above, the negative electrode utilization rate during charging and discharging is preferably 93% or more and 99% or less. If the negative electrode utilization rate is in the range of 93% or more, the initial charge efficiency does not decrease and the battery capacity can be greatly improved. In addition, if the negative electrode utilization rate is in the range of 99% or less, Li does not precipitate and safety can be ensured.
[0125] Moreover, mobile terminals, electric power vehicles, and power storage systems equipped with the nonaqueous electrolyte secondary battery are preferable because the nonaqueous electrolyte secondary battery has a high battery capacity, good cycle characteristics, and good initial efficiency. EXAMPLES
[0126] The present invention will be described in more detail below by showing examples and comparative examples of the present invention, but the present invention is not limited to these examples.
[0127] (Example 1-1) The laminate film type lithium ion secondary battery 30 shown in FIG. 3 was fabricated by the following procedure.
[0128] First, the positive electrode was prepared. The positive electrode active material was lithium nickel cobalt aluminum composite oxide (LiNi 0.7 Co 0.25 Al 0.05 A positive electrode mixture was prepared by mixing 95 parts by mass of ethylenediaminetetraacetate (FeO), 2.5 parts by mass of a positive electrode conductive assistant (acetylene black), and 2.5 parts by mass of a positive electrode binder (polyvinylidene fluoride, PVDF). The positive electrode mixture was then dispersed in an organic solvent (N-methyl-2-pyrrolidone, NMP) to form a paste-like slurry. The slurry was then applied to both sides of the positive electrode current collector using a coating device with a die head, and dried using a hot air drying device. At this time, a positive electrode current collector with a thickness of 15 μm was used. Finally, compression molding was performed using a roll press.
[0129] Next, the negative electrode was prepared. First, the negative electrode active material (silicon-based active material) was prepared as follows. A raw material (vaporized starting material) made by mixing metal silicon and silicon dioxide was placed in a reactor, and the material was vaporized in an atmosphere of a vacuum degree of 10 Pa and deposited on an adsorption plate. After sufficient cooling, the deposit was taken out and pulverized with a ball mill. Next, lithium was inserted into the silicon compound particles by an oxidation-reduction method for the silicon compound to modify it. First, the negative electrode active material particles were immersed in a solution (solution A) in which lithium pieces and naphthalene, an aromatic compound, were dissolved in tetrahydrofuran (hereinafter referred to as THF). This solution A was prepared by dissolving naphthalene in a THF solvent at a concentration of 0.2 mol / L, and then adding lithium pieces of 12 mass% by mass to the mixture of THF and naphthalene. In addition, the temperature of the solution in which the negative electrode active material particles were immersed was 20°C, and the immersion time was 20 hours. Then, the negative electrode active material particles were filtered out. By the above treatment, lithium was inserted into the negative electrode active material particles.
[0130] Next, the Li compound was stabilized by heat treatment at 650°C or less for 24 hours in an argon atmosphere. After that, the obtained silicon compound particles were coated with a carbon film by pyrolytic CVD. The pyrolytic CVD conditions were 595°C, acetylene gas was used as the hydrocarbon gas, and the treatment was carried out for 3 hours. Under these CVD conditions, the amount of carbon film coated and the G-band peak position were adjusted.
[0131] In this manner, the negative electrode active material particles were modified. By the above-described treatment, the negative electrode active material particles were produced.
[0132] The obtained negative electrode active material particles were subjected to XRD measurement, Raman spectroscopy, and particle size distribution measurement. For the gas generation test, 0.5 g of silicon-based active material was dispersed in 4.5 g of pure water to prepare a dispersion liquid, and the entire amount was sealed in an aluminum laminate pack. The volume [cc] immediately after sealing was taken as the reference value, and the pack was stored at 25°C. The reference value was subtracted from the volume value [cc] after 24 hours (first day), and the obtained value was divided by the weight of the dispersion liquid (5 g) to obtain the gas generation amount [cc / g]. The volume of the sealed laminate pack was measured by the Archimedes method.
[0133] The silicon-based active material prepared as above was mixed with a carbon-based active material in a mass ratio of 2:8 to prepare a negative electrode active material. Here, as the carbon-based active material, a mixture of natural graphite and artificial graphite coated with a pitch layer in a mass ratio of 5:5 was used. The median diameter of the carbon-based active material was 20 μm.
[0134] Next, the negative electrode active material, conductive additive 1 (carbon nanotubes, CNT), conductive additive 2 (carbon particles with a median diameter of about 50 nm), styrene butadiene rubber (styrene butadiene copolymer, hereinafter referred to as SBR), and carboxymethyl cellulose (hereinafter referred to as CMC) were mixed in a dry mass ratio of 92.5:1:1:2.5:3, and then diluted with pure water to form a negative electrode mixture slurry. The above SBR and CMC are negative electrode binders (negative electrode binding agents).
[0135] In addition, electrolytic copper foil (thickness 15 μm) was used as the negative electrode current collector. Finally, the negative electrode mixture slurry was applied to the negative electrode current collector and dried at 100° C. for 1 hour in a vacuum atmosphere. After drying, the deposition amount of the negative electrode active material layer per unit area on one side of the negative electrode (also called the area density) was 5 mg / cm. 2 It was.
[0136] Next, fluoroethylene carbonate (FEC), ethylene carbonate (EC), and diethyl carbonate (DEC) were mixed as a solvent, and then an electrolyte salt (lithium hexafluorophosphate: LiPF 6 ) was dissolved to prepare an electrolyte solution. In this case, the solvent composition was FEC:EC:DEC = 1:2:7 in volume ratio, and the content of the electrolyte salt was 1.0 mol / kg relative to the solvent. Furthermore, 1.5 mass% of vinylene carbonate (VC) was added to the obtained electrolyte solution.
[0137] Next, a secondary battery was assembled as follows. First, an aluminum lead was ultrasonically welded to one end of the positive electrode current collector, and a nickel lead was welded to the negative electrode current collector. Next, the positive electrode, separator, negative electrode, and separator were laminated in this order and wound in the longitudinal direction to obtain a wound electrode body. The end of the winding was fixed with a PET protective tape. The separator used was a laminated film of 12 μm in which a film mainly composed of porous polypropylene was sandwiched between a film mainly composed of porous polyethylene. Next, the electrode body was sandwiched between the exterior members, and then the outer peripheral edges except for one side were heat-sealed to store the electrode body inside. The exterior member used was an aluminum laminate film in which a nylon film, aluminum foil, and a polypropylene film were laminated. Next, the adjusted electrolyte was injected from the opening, impregnated under a vacuum atmosphere, and then heat-sealed and sealed.
[0138] The cycle characteristics and initial charge / discharge characteristics of the secondary battery thus fabricated were evaluated.
[0139] The cycle characteristics were investigated as follows. First, in order to stabilize the battery, two cycles of charging and discharging were performed at 0.2C in an atmosphere of 25°C, and the discharge capacity of the second cycle was measured. Next, charging and discharging were performed until the total number of cycles reached 299, and the discharge capacity was measured each time. Finally, the discharge capacity of the 300th cycle obtained by charging and discharging at 0.2C was divided by the discharge capacity of the second cycle to calculate the capacity retention rate (hereinafter also simply referred to as the retention rate). In the normal cycles, that is, from the third cycle to the 299th cycle, charging and discharging were performed at 0.7C for charging and 0.5C for discharging.
[0140] When investigating the initial charge / discharge characteristics, the initial efficiency (hereinafter sometimes referred to as initial efficiency) was calculated. The initial efficiency was calculated from the formula: initial efficiency (%) = (initial discharge capacity / initial charge capacity) x 100. The atmospheric temperature was the same as when investigating the cycle characteristics.
[0141] (Examples 1-2 to 1-4, Comparative Example 1-1) A secondary battery was manufactured and evaluated in the same manner as in Example 1-1, except that the G-band peak position was adjusted by changing the CVD conditions. The G-band peak position can be adjusted by the CVD temperature. As shown in Table 1, the G-band peak position was adjusted from 1530 to 1590 cm -1 The amount of gas generation on the first day could be suppressed at 1590 cm. Since there was no gas generation, the slurry was stable, and as a result, good initial efficiency and capacity retention were obtained. On the other hand, the one produced at the CVD temperature described in Comparative Example 1-1 had a G-band peak at 1590 cm. -1 The shape of the Raman chart also changed, and the diamond-like structure was no longer observed. 2 SiO 3 The half-width of the peak became larger than 3°, and the Si(220) crystallite size became smaller than 1 nm, and the amount of gas generation on the first day could not be suppressed. [Table 1]
[0142] (Examples 2-1 to 2-4, Comparative Example 2-1) As shown in Table 2, except that the amount of carbon coating was adjusted, a secondary battery was manufactured in the same manner as in Example 1-1, and each evaluation was performed. This can be adjusted by adjusting the processing time during pyrolysis CVD. When the amount of carbon coating is 0.5 mass% or less, the amount of carbon is too small, so the amount of gas generated on the first day could not be suppressed. In addition, the conductivity is not obtained, and the battery characteristics deteriorate. On the other hand, when the amount of carbon coating exceeds 0.5 mass%, the silicon-based active material can be sufficiently coated, so the amount of gas generated on the first day can be suppressed. In addition, good conductivity can be obtained, so good battery characteristics can be obtained. When the amount of carbon coating is more than 10 mass%, the amount of gas generated on the first day can be suppressed, but this leads to a decrease in battery capacity, and as a result, the battery characteristics deteriorate. From the above, the amount of carbon coating is preferably in the range of more than 0.5 mass% and 10 mass% or less. [Table 2]
[0143] (Examples 3-1 to 3-4) As shown in Table 3, except that the intensity of each peak component obtained by Raman spectroscopy was adjusted, a secondary battery was manufactured and each evaluation was performed in the same manner as in Example 1-1. This can be adjusted by adjusting the CVD conditions of the pyrolysis CVD. For example, by adjusting the temperature during pyrolysis CVD, the IB intensity can be adjusted, and as a result, ID / IB and IG / IB can be adjusted. In addition, by lowering the CVD rate, such as by lowering the pressure, ID can be lowered and IG can be raised. As a result, ID / IG and ISi / IG can be adjusted.
[0144] The amount of gas generated on the first day could be suppressed when ID / IB was in the range of 1.0 to 2.0 and IG / IB was also in the range of 1.0 to 2.0. The amount of gas generated on the first day could also be suppressed when ID / IG was in the range of 0.5 to 1.5 and Isi / IG was in the range of 0 to 2.0 (especially in the range of 0.7 to 2.0). If the Isi / IG value is 2.0 or less, there are few areas that are not covered with carbon, and gas generation can be suppressed effectively. [Table 3]
[0145] (Example 4-1 to Example 4-2) Next, as shown in Table 4, a secondary battery was manufactured and each evaluation was performed in the same manner as in Example 1-1, except that the true density of the coated carbon was adjusted. The true density of the carbon-coated silicon-based active material particles can be adjusted by adjusting the true density of the coated carbon. The true density of the coated carbon can be adjusted by adjusting the type and concentration of the gas supplied during pyrolysis CVD.
[0146] The true density of the coated carbon is 1.4 to 1.9 g / cm 3 At this time, the carbon-coated silicon-based active material has a true density of 2.0 to 2.5 g / cm 3The amount of gas generated on the first day was suppressed. The IUPAC classification of the materials of Examples 4-1 and 4-2, judged from the shape of the isothermal adsorption curve, was type II or type III. All of these showed good results in the initial efficiency, cycle characteristics, and gas generation test. [Table 4]
[0147] (Example 5-1 to Example 5-5) Next, secondary batteries were produced and evaluated in the same manner as in Example 1-1, except that the BET specific surface area of the negative electrode active material particles was adjusted as shown in Table 5. The BET specific surface area can be adjusted by adjusting the CVD conditions (gas type, pressure, flow rate) during pyrolysis CVD.
[0148] BET specific surface area is 0.5m 2 If the BET is 5m / g or more, the amount of gas generated on the first day can be suppressed, and better battery characteristics can be obtained. 2 When the concentration exceeded 100 mg / g, the amount of gas generated on the first day was slightly higher. [Table 5]
[0149] (Examples 6-1 to 6-8) Next, as shown in Table 6, except that the D50 (median diameter) of the silicon compound particles was changed, secondary batteries were manufactured and evaluated in the same manner as in Example 1-1. If the median diameter of the silicon compound is 0.5 μm or more, particularly 3 μm or more, the amount of gas generated on the first day can be suppressed, and good battery characteristics can be obtained. If the median diameter is 20 μm or less, the amount of gas generated on the first day can be suppressed, and good battery characteristics can be obtained. If the median diameter is 20 μm or less, the amount of expansion of the silicon compound particles during charging does not become too large, and physical and electrical destruction of the negative electrode active material layer due to expansion can be prevented. [Table 6]
[0150] The present specification includes the following aspects. [1]: A negative electrode active material for a non-aqueous electrolyte secondary battery, comprising negative electrode active material particles, The negative electrode active material particles are made of a silicon compound (SiO x : 0.5 ≦ x ≦ 1.6) containing silicon compound particles, The silicon compound particles contain a Li compound, the negative electrode active material particles have at least a part of their surface covered with a carbon material, The carbon material has a peak at 1530 cm due to the G band in Raman spectroscopy. -1 ~1590cm -1 and The amount of the carbon material coated is more than 0.5% by mass and 10% by mass or less with respect to the total mass of the silicon compound particles and the carbon material, A negative electrode active material for a non-aqueous electrolyte secondary battery, wherein a part or the whole of the carbon material is diamond-like carbon. [2]: The negative electrode active material for a nonaqueous electrolyte secondary battery according to [1] above, wherein the ratios of a G-band peak intensity IG, which is the intensity of a peak derived from a G band, a D-band peak intensity ID, which is the intensity of a peak derived from a D band, and a peak intensity IB at the midpoint between the G-band peak and the D-band peak, are 1≦ID / IB≦2 and 1≦IG / IB≦2, respectively, in Raman spectroscopic analysis of the negative electrode active material particles. [3]: The negative electrode active material for a nonaqueous electrolyte secondary battery according to the above [1] or [2], wherein an intensity ratio ID / IG of a D-band peak intensity ID, which is the intensity of a peak derived from a D band, to a G-band peak intensity IG, which is the intensity of a peak derived from a G band, in Raman spectroscopic analysis of the negative electrode active material particles, is 0≦ID / IG≦1.5. [4]: The negative electrode active material for a nonaqueous electrolyte secondary battery according to any one of [1] to [3] above, wherein the intensity ratio ISi / IG of a Si peak intensity ISi, which is the intensity of a peak derived from Si, and a G band peak intensity IG, which is the intensity of a peak derived from a G band, in Raman spectroscopic analysis of the negative electrode active material particles, is 0≦ISi / IG≦2.0. [5]: the true density of the negative electrode active material particles is 2.0 to 2.5 g / cm 3 The negative electrode active material for a non-aqueous electrolyte secondary battery according to any one of the above [1] to [4], [6]: the true density of the carbon material of the negative electrode active material particles is 1.4 to 1.9 g / cm 3 The negative electrode active material for a non-aqueous electrolyte secondary battery according to any one of the above [1] to [5], [7]: The negative electrode active material for a nonaqueous electrolyte secondary battery according to any one of [1] to [6] above, wherein the negative electrode active material particles have an adsorption / desorption isotherm obtained by nitrogen gas adsorption / desorption isotherm measurement that exhibits characteristics of Type II or Type III in the IUPAC classification. [8]: The negative electrode active material particles have a specific surface area of 0.5 m 2 / g or more 5.0m 2 The negative electrode active material for a non-aqueous electrolyte secondary battery according to any one of the above [1] to [7], wherein the negative electrode active material has a molecular weight of 100 / g or less. [9]: Li obtained by X-ray diffraction of the negative electrode active material 2 SiO 3 The negative electrode active material for a nonaqueous electrolyte secondary battery according to any one of [1] to [8] above, wherein the half width of a peak attributable to a peak in the vicinity of 2θ=18.7° is 0.5° or more and 3.0° or less.
[10] : The negative electrode active material for a nonaqueous electrolyte secondary battery according to any one of [1] to [9] above, wherein the crystallite size resulting from the Si(220) crystal plane obtained by X-ray diffraction of the negative electrode active material is 1 nm or more and 5 nm or less.
[11] : The negative electrode active material for a non-aqueous electrolyte secondary battery according to any one of [1] to
[10] above, wherein the silicon compound particles have a median diameter of 0.5 μm or more and 20 μm or less.
[12] : A non-aqueous electrolyte secondary battery comprising the negative electrode active material for non-aqueous electrolyte secondary batteries according to any one of [1] to
[11] above.
[13] : A mobile terminal comprising the nonaqueous electrolyte secondary battery according to
[12] above.
[14] : An electric power vehicle comprising the nonaqueous electrolyte secondary battery according to
[12] above.
[15] : A power storage system comprising the nonaqueous electrolyte secondary battery according to
[12] above.
[16] : Silicon compounds (SiO x : 0.5≦x≦1.6) and preparing silicon compound particles comprising the same; A step of coating at least a portion of the silicon compound particles with a carbon material; Inserting Li into the silicon compound particles; a method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery, comprising the steps of: producing a negative electrode active material particle by the above-mentioned method; and producing a negative electrode active material for a non-aqueous electrolyte secondary battery using the negative electrode active material particle; The amount of the carbon material coated is more than 0.5% by mass and not more than 10% by mass with respect to the total mass of the silicon compound particles and the carbon material in the negative electrode active material particles to be produced, The carbon material is coated on the negative electrode active material particles to produce a peak attributable to the G band in Raman spectroscopy of the carbon material at 1530 cm -1 ~1590cm -1 and performing the process under conditions in which a part or all of the carbon material becomes diamond-like carbon.
[0151] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention. [Explanation of symbols]
[0152] 10...Negative electrode, 11...Negative electrode current collector, 12...Negative electrode active material layer, 20...Li-doped reformer (bulk reformer), 21...positive electrode (lithium source, reforming source), 22...Silicon compound particles (silicon oxide powder), 23...organic solvent, 24...separator, 25...powder storage container, 26...power supply, 27...bathtub, 30...Lithium ion secondary battery (laminate film type), 31...electrode body, 32...Positive electrode lead (positive electrode aluminum lead), 33...Negative electrode lead (negative electrode nickel lead), 34...adhesive film, 35...exterior part.
Claims
1. A negative electrode active material for a non-aqueous electrolyte secondary battery, comprising negative electrode active material particles, The negative electrode active material particles are made of a silicon compound (SiO x : 0.5≦x≦1.6), The silicon compound particles contain a Li compound, the negative electrode active material particles have at least a part of their surface covered with a carbon material, The carbon material has a peak at 1530 cm due to the G band by Raman spectroscopy. -1 ~1590cm -1 and The amount of the carbon material coated is more than 0.5% by mass and 10% by mass or less with respect to the total mass of the silicon compound particles and the carbon material, A negative electrode active material for a non-aqueous electrolyte secondary battery, wherein a part or the whole of the carbon material is diamond-like carbon.
2. 2. The negative electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, wherein a ratio of a G-band peak intensity I, which is the intensity of a peak derived from a G band, a D-band peak intensity I, which is the intensity of a peak derived from a D band, and a peak intensity I, which is the intensity of a peak at a midpoint between the G-band peak and the D-band peak, satisfies 1≦I / I≦2 and 1≦I / I≦2, respectively.
3. 2. The negative electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, wherein an intensity ratio ID / IG of a D-band peak intensity ID, which is an intensity of a peak derived from a D band, and a G-band peak intensity IG, which is an intensity of a peak derived from a G band, in Raman spectroscopic analysis of the negative electrode active material particles satisfies 0≦ID / IG≦1.
5.
4. 2. The negative electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, wherein an intensity ratio I / IG of a Si peak intensity I, which is an intensity of a peak derived from Si, and a G band peak intensity IG, which is an intensity of a peak derived from a G band, in Raman spectroscopic analysis of the negative electrode active material particles, is 0≦I / IG≦2.
0.
5. The true density of the negative electrode active material particles is 2.0 to 2.5 g / cm 3 2. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1,
6. The true density of the carbon material of the negative electrode active material particles is 1.4 to 1.9 g / cm 3 2. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1,
7. 2. The negative electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, wherein an adsorption / desorption isotherm obtained by nitrogen gas adsorption / desorption isotherm measurement has characteristics of Type II or Type III in the IUPAC classification.
8. The negative electrode active material particles have a specific surface area of 0.5 m 2 / g or more 5.0m 2 2. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the molecular weight of the negative electrode active material is 1 / g or less.
9. Li obtained by X-ray diffraction of the negative electrode active material 2 SiO 3 2. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein a half-width of a peak attributable to the peak in the vicinity of 2θ=18.7° is 0.5° or more and 3.0° or less.
10. 2. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the crystallite size due to the Si (220) crystal plane obtained by X-ray diffraction of the negative electrode active material is 1 nm or more and 5 nm or less.
11. 2. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the silicon compound particles have a median diameter of 0.5 μm or more and 20 μm or less.
12. A non-aqueous electrolyte secondary battery comprising the negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 .
13. A mobile terminal comprising the nonaqueous electrolyte secondary battery according to claim 12.
14. An electric power vehicle comprising the nonaqueous electrolyte secondary battery according to claim 12.
15. A power storage system comprising the nonaqueous electrolyte secondary battery according to claim 12.
16. Silicon compounds (SiO x : 0.5≦x≦1.6), A step of coating at least a portion of the silicon compound particles with a carbon material; Inserting Li into the silicon compound particles; a method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery, comprising the steps of: producing a negative electrode active material particle by the above-mentioned method; and producing a negative electrode active material for a non-aqueous electrolyte secondary battery using the negative electrode active material particle; The amount of the carbon material coated is more than 0.5 mass % and not more than 10 mass % with respect to the total mass of the silicon compound particles and the carbon material in the negative electrode active material particles to be produced, The carbon material is coated on the negative electrode active material particles to produce a peak attributable to the G band in Raman spectroscopy of the carbon material at 1530 cm -1 ~1590cm -1 and performing the process under conditions in which a part or all of the carbon material becomes diamond-like carbon.
Citation Information
Patent Citations
Silicon-oxygen material, negative electrode material and preparation method therefor, and lithium ion battery
EP4231379A1
Negative electrode material for secondary batteries, and nonaqueous electrolyte secondary battery using the same
JP2017120710A
Anode material, and electrochemical and electronic devices containing the same
JP2022517789A
Nonaqueous electrolytic secondary battery and its manufacture
JP1994325765A
Lithium secondary battery
JP2001185127A